Here's what I have so far - x – 3 = 2x – 13 simplify = x – 3 + 3 = 2x – 13 + 3 now we have = x = 2x - 10 Now I'm stuck!
can you draw the diagram here please
What do you mean "diagram". This problem doesn't have one....
ok i'll figure it out
I still don't understand.
what you have above is correct to continue put the variable on one side the number on the other
How do I remove 2x from the equation?
but how do I simplify that farther?
divide each side by -1 x = 10
so I do x - 2x = 2x - 10 - 2x which equals x - 2x = 10 then I divide by -1 (where did you get the -1 from?)
so it's x * -2x? I multiply each side by -2x? How do you make 2x negative?
1x -2x = -1 x no number before the variable is understood as 1
okay. so x =1 which equals 1x.
I have no idea what that means....
x -2x subtract 1x - 2x = -1x
read it again slower it shows examples that 1 is understood
okay just a min
Oh I get it! x - 2x = 1x - 2x = -1x = -x -x = -10 and two negatives = a positive so x = 10
Thanks so much!